2019
DOI: 10.12740/pp/102656
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic differences and symptoms stability in unipolar and bipolar depression. Medical charts review in 99 inpatients

Abstract: Cel pracyPóźna rozpoznawalność choroby afektywnej dwubiegunowej (CHAD) może skutkować m. in. prowadzeniem nie w pełni adekwatnego leczenia, zwiększeniem cierpienia związanego z chorobą oraz ryzyka zachowań suicydalnych, a także wzrostem kosztów prowadzonej terapii. Brak sprawdzonych w warunkach klinicznych biomarkerów dwubiegunowości kieruje uwagę klinicystów na analizę przebiegu choroby i symptomatologii depresji w przebiegu CHAD. Celem niniejszej pracy była retrospektywna analiza różnic występowania i powtar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
3
4
0
2
Order By: Relevance
“…Those findings highlight the potential of reward processing deficits related to anhedonia to be trait factors of mood disorders. Interestingly, a recent study demonstrated that anhedonia was more frequent in BD patients compared to MDD patients [34], which is in line with our current findings but opposite to an earlier investigation reported that unipolar depressed patients exhibited greater severity of anhedonia [35]. However, most previous studies did not use specialized tools to assess anhedonia, and this might be the main explanation for the existing discrepancy.…”
Section: Discussionsupporting
confidence: 79%
“…Those findings highlight the potential of reward processing deficits related to anhedonia to be trait factors of mood disorders. Interestingly, a recent study demonstrated that anhedonia was more frequent in BD patients compared to MDD patients [34], which is in line with our current findings but opposite to an earlier investigation reported that unipolar depressed patients exhibited greater severity of anhedonia [35]. However, most previous studies did not use specialized tools to assess anhedonia, and this might be the main explanation for the existing discrepancy.…”
Section: Discussionsupporting
confidence: 79%
“…7 The relative stability of suicidal ideation across depressive episodes has been replicated in bipolar disorder. 12 Other studies, however, have found sleep disturbance and concentration difficulties to be the most stable symptoms, 13 or all symptoms to have equally low stability. [4][5][6] These inconsistencies and low stability estimates may be influenced by both study design (small samples) and psychometric limitations of the measures used to quantify consistency (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, previous studies have indicated high consistency for anhedonia, at least between two consecutive episodes. 7,13…”
Section: Discussionmentioning
confidence: 99%
“…According to some researchers, there are certain groupings of serotonin neurons in the brain that are over-active in people suffering from depression [ 33 ]. Interestingly, features of increased impulsivity were observed in analyses of symptoms of depressive disorders [ 34 ]. Clinically, drugs affecting serotonergic transmission can be used in the prevention of impulsive and aggressive behavior [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%